Analysis of The Government's Internal Control System on Fund Management in Swatani Village, Rilau Ale District, Bulukumba District - Faidah, Rani Nurul; Sahade; Samsinar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
: This research aims to find out whether the Government Internal Control System meets the principles according to Government Regulation Number 60 of 2008 concerning the Government Internal Control System. Variables in this research are attributes or traits or values of people, objects, or activities that have certain variations determined by the researcher to be studied and conclusions drawn. The samples in this research are documents relating to the government's internal control system for managing funds in Swatani Village, Rilau Ale District, Bulukumba Regency. Documentation relating to internal control activities implemented in Swatani Village, Rilau Ale District, Bulukumba Regency. This research uses qualitative data analysis techniques with descriptive analysis methods. The results of the analysis carried out in Swatani Village, Rilau Ale District, Bulukumba Regency where in the implementation of PP No. 60 of 2008 there are still articles that have not been implemented, it is proven that there are still 4 articles out of 10 articles that have not been implemented optimally in Swatani Village, namely a review of the performance of government agencies concerned with article 18 paragraph 3 where the village government has not been optimal in tracing and evaluating the problems that arise during SPJ inspections, human resource development article 20 paragraphs 2a and 2b because the development of employees is lacking, resulting in the management of village funds not running effectively and efficient, and control over the information system article 21 paragraph 2a where managing village funds is carried out using the Siskeudes and Omspan applications for control which is not yet optimal, and Determination of reviews of performance indicators and measures article 35 2a and 2c where the village government looks at performance measures with timeliness, discipline , responsibility, seriousness and neatness. This shows that SPI in managing village funds is not optimal in accordance with SPIP principles.